Analisis Faktor Yang Mempengaruhi Industri Kecil Menengah Tekstil Di Provinsi Jawa Timur - Gusminto, Ajeng Pangesti Muttaqiina; Sitohang, Arga Christian (Nirta Learning Centre, 2024)
The aim of this research is to analyze the influence of labor absorption, population and investment on Small and Medium Textile Industries in East Java Province. This research uses a descriptive quantitative approach with time series data 2016-2023, the data used is secondary data taken by the East Java Province Department of Industry and Trade and the East Java Province Central Statistics Agency with multiple linear regression analysis techniques interpreted using Eviews 12. Results from T test research on the labor absorption variable has a significant effect while the population and investment variables have no significant effect. The F test results of the labor absorption, population and investment variables have a simultaneous influence on the Small and Medium Textile Industry in East Java Province. From the results of the determinant test (R2), the independent variable is 71.7%, while the remaining 28.3% is influenced by other variables from this research.